Living Next to an Aggressor: Willingness to defend One’s Country in Lithuania, Latvia, and Taiwan - Ramonaitė, Ainė; Šlekys, Deividas; Tylaitė, Aurelija (Politologija, 2025)
What determines the willingness to defend one’s country in states that live next to an aggressive neighbor? This article analyzes three countries with similar geopolitical situations – Lithuania, Latvia, and Taiwan. The aim of the article is to assess the level of willingness to defend one’s country and the factors influencing it in Lithuania, Latvia, and Taiwan, based on public opinion surveys conducted in all three countries. The article is divided into three parts. The first part discusses the historical, cultural, and sociopolitical similarities of the three countries under examination. The second part evaluates the defense policies of the three countries and the role of society in them. The third part is dedicated to analyzing the survey data. It first presents the data and measurement instruments, then discusses the level of willingness to defend the country according to four indicators, and finally presents the results of a regression analysis that examines the factors influencing the will to defend.
Keywords: willingness to defend one's country; Taiwan; Lithuania; Latvia; total defense; survey